Fertilizantes de eficiência aprimorada: perspectivas e potencial de uso de biopolímeros como matrizes de liberação lenta ou controlada - Borelli, Laíze Matos (Universidade Federal de São Carlos, 2020)
Conventional mineral fertilizers consist of products applied in the field, which aim to provide higher yields for agricultural crops. However, the excessive use of these fertilizers in the soil causes environmental, economic, and energy problems, encouraging the search for alternatives in order to mitigate the harmful effects. Thus, one of the proposed strategies was the introduction of improved efficiency fertilizers in agriculture. The industrial production of these fertilizers generally involves the use of synthetic polymers, which, despite having good agronomic results, promote the generation of residues in the soil, as well as presenting a high price in the consumer market. In order to overcome this situation, recent research reports the use of several natural and biodegradable sources in the development of fertilizers, in particular biopolymers. However, despite these studies addressing the characterization of fertilizers and assessing their nutrient release profile and the degree of swelling in liquid media, it is noted that the scientific literature still lacks relevant information, such as its application in agricultural systems and data evaluation about crops, which enable the effective application of these technologies.
Improved efficiency fertilizers: prospects and potential for using biopolymers as slow or controlled release matrices
Keywords: Biopolímeros; Fertilizantes; Fertilizantes de eficiência aprimorada; Produção de fertilizantes; Tecnologias; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA